PENGARUH PEMBERIAN DAGING BUAH DURIAN ( Durio Zibethinus ) TERHADAP FUNGSI GINJAL (UREUM DAN KREATININ) TIKUS PUTIH ( Rattus Norvegicus L.) JANTAN GALUR WISTAR - ALAMSYAH, RAJA IQBAL; ASFUR, ROBITAH (LP2MTBM MAKARIOZ, 2024)
Examination of serum urea and creatinine levels is important to determine the physiological condition of the kidneys. Patients with kidney disease, especially those with kidney failure, are strongly advised to maintain a pattern of consuming durian, high levels of potassium in durian can be at risk of experiencing hyperkalemia. Consuming durian which is high in potassium will be one of the factors for the occurrence of AKI. The most famous durian fruit species in Indonesia is Durio zibethinus. Durian comes from the forests of Sumatra, Malaysia and also Kalimantan which are wild plants. To determine the effect of giving durian (Durio Zibethinus) pulp on changes in kidney function (creatinine and urea) in male white rats (Rattus Norvegicus L) Wistar strain. True Experiment with a